Effect of sulphur, zinc and boron application on productivity, quality, and profitability of Indian mustard in Bundelkhand region - Narendra Kumar Bhinda; Yogeshwar Singh (Annals of Agricultural Research, 2023)
A field experiment was conducted to determine the impact of sulphur (S), zinc (Zn) and boron (B) on productivity, quality and profitability of Indian mustard during 2019-20 at Rani Lakshmi Bai Central Agricultural University, Jhansi, Uttar Pradesh. The experiment laid out in split plot design (SPD) with three level of S as in main plot viz., 0, 20 and 40 kg S ha-1 and six level of Zn and B viz., Control, 2.5 kg Zn, 5.0 kg Zn, 0.5 kg B ha-1, 1.0 kg B ha-1 and 2.5 kg Zn + 0.5 kg B ha-1 as in sub-plot and replicated thrice. Experimental data revealed that application of 40 kg S ha-1 significantly increased seed yield, stover yield, harvest index and oil content by 21.0, 7.20, 9.63 and 30.1 per cent, respectively over 0 kg S ha-1. Moreover, the same treatment recorded highest yield attributes viz. siliqua plant-1 (180), seeds siliqua-1 (11.8), 1000-seed weight (5.14 g), seed yield (1.84 t ha-1), stover yield (4.91 t ha-1), harvest index (27.3%) and oil content (40.1%) of Indian mustard. Among Zn and B levels, maximum yield attributes viz. siliqua plant-1 (176), seeds siliqua-1 (11.7), 1000-seed weight (5.09 g), seed yield (1.79 t ha-1), stover yield (4.86 t ha-1) and harvest index (26.9%) were recorded with combined application of 2.5 kg Zn + 0.5 kg B ha-1. However, higher oil content (39.6%) was recorded under application of 5 kg Zn ha-1. The maximum net returns and B: C ratio was registered with application of 40 kg S ha-1 along with 2.5 kg Zn + 0.5 kg B ha-1.